Redescription of Parotocinclus bahiensis (Miranda-Ribeiro, 1918) (Pisces, Ostariophysi, Loricariidae) - Britski, Heraldo A.; Garavello, Julio Cesar (Zootaxa, 2009)
Microlepidogaster bahiensis Miranda-Ribeiro (1918), assigned to Parotocinclus Eigenmann & Eigenmann, 1889, by Garavello (1977), was described in a short and uninformative way which does not allow for its distinction from other species of Parotocinclus; besides, the two syntypes of the species are regarded as lost. For these reasons a neotype is herein designated and a detailed description of the species is presented based on topotypes. The species is characterized by the combination of the following features: scapular bridge almost completely exposed ventrally, arrector fossae, when present, small or very reduced; abdomen covered by 5–7 wide lateral plates on each side and very small platelets in between, leaving abundant naked areas surrounding them; a small group of larger plates in front of anus; caudal peduncle ellipsoid in cross section; total plates in median series 21–23; longitudinal series with 23–26 plates; 18–29 teeth on premaxillary and 12–24 on dentary; it can also be distinguished by its characteristic caudal-fin color pattern. Features that allow us to assign the species to Parotocinclus and a hypothesis about its relationships with other species of the genus are also presented.